Criteria and methodology of complex evaluation of bituminous concrete mixer quality/Asfaltbetonio maišytuvo kokybės kompleksinio vertinimo kriterijai ir metodika - Sivilevičius, Henrikas (Journal of Civil Engineering and Management, 2001)
The structure and sequence of technological operations of mixers for bituminous concrete mixtures, functioning in Lithuanian bituminous concrete mixing plants have been analyzed. The problems, which are subject to interest by the owners of bituminous concrete mixers, have been systematized. The necessity and objectives of quality evaluation of the functioning bituminous concrete mixers have been proved. A new multi-criteria mathematical model for determining quality of bituminous concrete – consisting of the sum of 4 group indicators, which evaluate quality of bituminous concrete mixture production in the mixer, environmental care, economy and technological universality – has been provided. The following 9 criteria make up the mathematical model, which can be used for calculation of quality indicator K of the working bituminous concrete mixer: accuracy of the bituminous concrete mixture content, produced in the mixer, ie the conformity of its component quantity with the project requirements (s); its temperature conformity with the temperature determined (t); its homogeneity in the batch, described by the mixing quality of batched components (h); environmental care, when the air is polluted by pollutants, thrown out from bituminous concrete (aa); bituminous concrete mixture production expenses as for one ton of (gi); level of physical and moral wear of the mixer (nl); expenses, needed for its maintenance and reconstruction (rr); use of its capacity when producing bituminous concrete mixture (pn); as well as technological universality of bituminous concrete mixer, ie ability to produce mixtures of different types and marks (tu). Coefficients of significance (importance) of all criteria are determined, using expert research methods. For this purpose a questionnaire for respondents (experts) has been prepared, which was filled by 43 scientists and production specialists, who have good knowledge of technology of bituminous concrete mixture production. The high value of concordation coefficient (W = 0,719) has shown good coordination of expert opinions, because X 2 = 247,5 is much higher than critical X 2 kr value with ε = 8 freedom level and 1% of accepted significance level, which makes up only 20,09. The experts believe that the most important criteria, reflecting the quality of bituminous concrete mixture are S([Xbar] j = 8,60), H([Xbar] j = 7,58), t(Xj = 7,3o), following in the range is the criterion AA (Xmac;j = 4,95), TU([Xbar]j = 4,56), GI([Xbar]j= 3,91), NL([Xbar]j = 3,47), and at the end least important RR([Xbar]j = 2,44) and PN([Xbar]j = 2,19). total sum of criteria is 45. The bituminous concrete mixer quality change when using it has been provided. The relation of its quality coefficient K reduction rhythm and level of conformity with the requirements imposed and constantly getting stricter has been analyzed.Article in Lithuanian.First Published Online: 30 Jul 2012